Relationship Between S100 Protein Expression and Grading Meningioma - Lale Maulin Prihatina; Rohadi; Bambang Priyanto; Decky Aditya Zulkarnaen; Abdul Syukur (Jurnal Penelitian Pendidikan IPA, 2025)
Meningioma is the most common type of benign brain tumor in adults and mostly originates from the meningeal layer of the brain and spinal cord. The prevalence of meningioma in the world is estimated to be about 24-30% of intracranial primary brain tumors. This tumor is classified into three groups based on grade, grade I (benign), grade II (atypical), and grade III (anaplastic). The S100 protein is not specific to meningiomas but some studies have shown that the expression of S100 protein is stronger in grade I meningiomas than in grade II and III meningiomas. Based on these findings, the authors are interested in analyzing whether there is a relationship between S100 expression and meningioma grading. The determination of S100 protein expression is very necessary as a reference in determining the prognosis and selection of the best therapy for patients. This research was carried out in the period from January 2021 to December 2021. 9 samples were included in this study according to the inclusion and exclusion criteria. The data was analyzed using SPSS version 26. The results of this study: A normality test was carried out with the Shapiro Wilk test and a value of p=0.34 (CI 95%) was obtained using Spearman analysis.